Why Women Are Not Talking About It: Reasons for Nondisclosure of Sexual Victimization and Associated Symptoms of Posttraumatic Stress Disorder and Depression. (March 2020) - Carson, Kaitlin Walsh; Babad, Sara; Brown, Elissa J.; Brumbaugh, Claudia Chloe; Castillo, Betzabe K.; Nikulina, Valentina
Disclosure of traumatic experiences is typically encouraged and associated with positive outcomes. However, there is limited research on nondisclosure of sexual trauma and consequent symptomology. This online study of undergraduate females examines reasons for nondisclosure and associated symptoms of posttraumatic stress disorder (PTSD) and depression. Of 221 participants who reported sexual victimization, 25% had not previously disclosed it. Four reasons for nondisclosure were identified: shame, minimization of experience, fear of consequences, and privacy. Nondisclosers who minimized the experience and nondisclosers low on shame reported fewer PTSD symptoms than disclosers. These findings suggest that reasons for nondisclosure are associated with symptomology.